2003
DOI: 10.1136/mp.56.5.256
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and genetic analysis of 65 patients with a clinical suspicion of X linked hyper-IgM

Abstract: Background: X linked hyper-IgM (XHIM) is a primary immunodeficiency caused by mutations in the tumour necrosis factor superfamily 5 gene, TNFSF5, also known as the CD40 ligand (CD40L) gene. Patients often present with recurrent infections, and confirmation of a diagnosis of XHIM enables appropriate therapeutic interventions, including replacement immunoglobulin, antibiotics, and bone marrow transplantation. Aim: To review and optimise the institution's diagnostic strategy for XHIM. Method: Samples from 65 boys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 23 publications
1
16
1
2
Order By: Relevance
“…In our patient, activation-induced CD40L surface upregulation was within the range of normality,5 albeit slightly less than the control. Perceived differences in the upregulation of surface CD40L between laboratories could be due to technical reasons, such as different affinities of monoclonal antibodies or the use of other reagents for CD40L detection (eg, CD40 Ig).…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…In our patient, activation-induced CD40L surface upregulation was within the range of normality,5 albeit slightly less than the control. Perceived differences in the upregulation of surface CD40L between laboratories could be due to technical reasons, such as different affinities of monoclonal antibodies or the use of other reagents for CD40L detection (eg, CD40 Ig).…”
Section: Discussioncontrasting
confidence: 43%
“…This was performed as previously described 5. Briefly, blood was collected from the patient and a control subject into tubes containing lithium heparin anticoagulant.…”
Section: Methodsmentioning
confidence: 99%
“…However, a few patients have low IgM levels, 45 indicating that this feature does not rule out a diagnosis of CD40L deficiency. Conversely, normal or even elevated IgA levels and (more rarely) IgG levels can sometimes be observed; this suggests the presence of a CD40-independent CSR pathway, which may operate upon stimulation of B cells through their BAFF or TACI receptors in the intestinal lamina propria 46 or Toll-like receptors in the marginal zone.…”
Section: Laboratory Test Resultsmentioning
confidence: 97%
“…The numbers of cases with low IgM differ strikingly between the studies. For example, Katz et al [14] and Levy et al [2] reported no cases with low IgM (n = 0/16 and n = 0/55, respectively), whereas Winkelstein et al [20] reported eight cases and Gilmour et al [21] reported four cases with low IgM (n = 8/56 and n = 4/17, respectively). Our global analysis of all of the results of Table 2 using two-tailed Fisher's exact test revealed that the IgM serum levels reported by the studies differ significantly (P = 0.004).…”
Section: Discussionmentioning
confidence: 93%